Improve Offensive Language Detection with Ensemble Classifiers - Ekinci, Ekin; Ilhan Omurca, Sevinc; Sevim, Semih (International Journal of Intelligent Systems and Applications in Engineering, 2020)
Sharing content easily on social media has become an important communication choice in the world we live. However, in addition to the conveniences it provides, some problems have been emerged because content sharing is not bounded by predefined rules. Consequently, oﬀensive language has become as a big problem for both social media and its users. In this article, detecting offensive language in short text messages on Twitter is aimed. As short texts do not include enough statistical information have drawbacks. To cope with these drawbacks of the short texts, semantic word expansion based on concepts and word-embeddings vectors are proposed. Then, for classification task, decision tree and decision tree based ensemble classifiers such as Adaptive Boosting, Bootstrap Aggregating, Random Forest, Extremely Randomized Decision Tree and Extreme Gradient Boosting algorithms are used. Also, the imbalanced dataset problem is solved by oversampling. Experiments on the dataset show that extremely randomized trees with word-embedding vectors as input achieved 85.66% F-score.